Customer Solution and Communication in Religious Tourism: A Penta-Helix Based Revitalization Strategy at "Syekh Wasil" Kediri - Ema Hakimah; Ratri Nugrahanti; Sri Aliami; Samari Samari (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: Describe the topic your paper examines. Provide a background to your paper and why is this topic interesting. Avoid unnecessary content. Background Problems: State the problem or economic/business phenomena studied in this paper and specify the research question(s) in one sentence. Novelty: Summarize the novelty of this paper. Briefly explain why no one else has adequately researched the question yet. Research Methods: Provide an outline of the research method(s) and data used in this paper. Explain how did you go about doing this research. Again, avoid unnecessary content and do not make any speculation(s). Finding/Results: List the empirical finding(s) and write a discussion in one or two sentences. Conclusion: Provide conclusion(s) and implication(s) of your research. What conclusions did you get and what are the implication(s)? What is the main take-home message?